Conceptualization of emotions in three medical systems: traditional chinese medicine, ayurveda and traditional mexican medicine - Nayelhi Itandehui Saavedra Solano (Revista Latinoamericana de Estudios sobre Cuerpos, Emociones y Sociedad)
The  emergence  of  alternative  and  complementary  medicines  (CAM)  to  address  emotional  upsets,  chronic  ailments and  achieving  overall wellness has  been  reported  in  several  countries.  Its  practices  generally  deal  with  the  psycho-physiological  and  the  spiritual  state.  Although  there  are  studies  concerning  different  aspects  about  CAM,  it  is  still little  the  information  on  the  concepts  of  person,  body  and  emotion  they  hold.  Therefore,  the  aim  of  this  paper  is to  determine  the conceptualization  of  emotions  in  traditional  chinese  medicine,  Ayurveda  and  traditional  mexican medicine. The information has been gathered on theoretical texts and works based in ethnographies. The three health practices conceptualize the body and emotions based on a vast symbolic world in which representations of the universe, nature and human beings are juxtaposed. The human being is represented as an interweaving of functions expressed materially (organs, tissue, etc.) and immaterially (energy, emotions, etc.). In order to come to understand the emotions we first need to know the macro cosmic development, because emotions are manifestation of the energies that produce all  forms  of  life.  Into  these  health  practices,  the  organic,  emotional  and  energetic  aspects  are  equally  important  for diagnosis and treatment.